2009
DOI: 10.1021/om801194h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Reactivity of Intramolecularly Coordinated Organoantimony and Organobismuth Sulfides

Abstract: Organoantimony(III) and organobismuth(III) sulfides, containing O,C,O-chelating ligands (L1−3 = 2,6-(ROCH2)2C6H3 −, where R = Me (L1), t-Bu (L2), or mesityl (L3)), [L1−3MS]2, where M = Sb (L1 (5), L2 (6), L3 (7)) or M = Bi (L2 (8)), were prepared by the reaction of parent organoantimony and organobismuth chlorides with Na2S·9H2O in toluene/water. All sulfides 5−8 were characterized by elemental analysis, electrospray ionization mass spectrometry, 1H and 13C NMR spectroscopy, and X-ray diffraction techniques. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 50 publications
3
19
0
3
Order By: Relevance
“…As (Larsen et al, 2001) B (Dostál et al, 2007c) Bi (Dostál et al, 2006a;Dostál et al, 2007c;Dostál et al, 2009b;Fridrichová et al, 2009;Chovancová et al, 2009) Co (Arrais et al, 2006) Cr and Fe (Martinez-Alvarez et al, 2004) Cr and Ru (Moret et al, 2005) Fe and Ru (Paim et al, 2005) Ge (Jirásko et al, 2009; Mo (Gun et al, 2003) Os (Dorcier et al, 2005;Dorcier et al, 2008;Schmid et al, 2007) Pb (Casas et al, 2004) Pd (Macchioni et al, 2003) Rh (Dorcier et al, 2008) Ru (Ang et al, 2006;Dorcier et al, 2005;Dorcier et al, 2008;Schmid et al, 2007) Se (Zhou et al, 2007) Sb (Dostál et al, 2006a;Dostál et al, 2007a;Dostál et al, 2007c;Dostál et al, 2008;Dostál et al, 2009a;Dostál et al, 2009b;Fridrichová et al, 2009;Chovancová et al, 2009;Machuča et al, 2007) Sn (Baul et al, 2005a;Baul et al, 2005b;Baul et al, 2005c;Baul et al, 2006a;Baul et al, 2006b;Baul et al, 2006c;Baul et al, 2006d;Baul et al, 2007a;Baul et al, 2007b;…”
Section: A Basic Ionization Mechanisms Of Organometallic Compoundsunclassified
See 1 more Smart Citation
“…As (Larsen et al, 2001) B (Dostál et al, 2007c) Bi (Dostál et al, 2006a;Dostál et al, 2007c;Dostál et al, 2009b;Fridrichová et al, 2009;Chovancová et al, 2009) Co (Arrais et al, 2006) Cr and Fe (Martinez-Alvarez et al, 2004) Cr and Ru (Moret et al, 2005) Fe and Ru (Paim et al, 2005) Ge (Jirásko et al, 2009; Mo (Gun et al, 2003) Os (Dorcier et al, 2005;Dorcier et al, 2008;Schmid et al, 2007) Pb (Casas et al, 2004) Pd (Macchioni et al, 2003) Rh (Dorcier et al, 2008) Ru (Ang et al, 2006;Dorcier et al, 2005;Dorcier et al, 2008;Schmid et al, 2007) Se (Zhou et al, 2007) Sb (Dostál et al, 2006a;Dostál et al, 2007a;Dostál et al, 2007c;Dostál et al, 2008;Dostál et al, 2009a;Dostál et al, 2009b;Fridrichová et al, 2009;Chovancová et al, 2009;Machuča et al, 2007) Sn (Baul et al, 2005a;Baul et al, 2005b;Baul et al, 2005c;Baul et al, 2006a;Baul et al, 2006b;Baul et al, 2006c;Baul et al, 2006d;Baul et al, 2007a;Baul et al, 2007b;…”
Section: A Basic Ionization Mechanisms Of Organometallic Compoundsunclassified
“…As (Florencio et al, 1997;Pedersen & Francesconi, 2000); Au (Dinger & Henderson, 1998a, b;Goss et al, 2003;Kilpin et al, 2007); Bi (Dostál et al, 2009b;Chovancová et al, 2009); Co (Alsberg et al, 2001); Fe (Henderson & Alley, 2002;KaneMaguire et al, 1996;Seiwert & Karst, 2007;Wu et al, 2008); Ge Takeuchi et al, 2006;; Hg (Nicholson & Whitley, 2004); Pb (Casas et al, 2004); Pd (Chevrin et al, 2007);…”
Section: Tandem Mass Spectra Of Organometallic Compoundsmentioning
confidence: 99%
“…Recently, Dostál and co-workers synthesized and structurally characterized monoarylantimony dihalides containing OCO pincer ligands 99a-c, 100a-b and 101a-b [22,61,84]. The 99a-c dichlorides were prepared via the lithiation of appropriate OCO pincer ligands with n-BuLi and subsequent reaction with SbCl 3 (Scheme 32).…”
Section: Halides(iii)mentioning
confidence: 99%
“…Treatment of the chlorides 99a-c and Na 2 S in toluene/water resulted in the formation of the corresponding organoantimony(III) sulfides 107a-c (Scheme 37) [84]. The single-crystal XRD analysis of sulfides 107a-c revealed that all three compounds are centrosymmetric dimmers with a planar central 4-membered Sb 2 S 2 ring.…”
Section: Organoantimony(iii) Suflides Carboxylates Triflates and Camentioning
confidence: 99%
“…However, the utilization of organobismuth compounds trivalent and pentavalent for organic synthesis is rarely reported partly due to the unstable nature of the Bi-C bonds [6,7]. Recent developments show that the incorporation of a bulky substituent in pentavalent organobismuth complex can result of organobismuth compounds that have stable Bi-C bonds [8][9][10]. In our research group, we have been working on the synthesis of stable pentavalent organobismuth compounds.…”
Section: Introductionmentioning
confidence: 99%